ANALISIS AGENDA SETTING PROSES PEMEKARAN WILAYAH KELURAHAN KADIPIRO, KECAMATAN BANJARSARI, KOTA SURAKARTA - Safira Janet Araminta; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2021)
The division of the Kadipiro Village area was a policy taken by the Surakarta City Government in 2017 as a way to overcome the large population and territorial problems in this area. However, in the formulation of this policy it is known that there are various problems, including the prblem of relatively small span of control in each village in Surakarta, the composition of staffing in the Regional Governmet of Surakarta is no longer proportional, and there is a provision for a minimum area as a requiremt for regional expansion which is not fulfilled. This study aims to analyze the agenda setting process in the regional expansion policy at Kadipiro and determine the agenda setting model in the policy making process. The research method is qualitative research with a descriptive approach. As for the data collection techniques carried out through interviews and analysis of supporting documents. The research showed that the agenda setting process in the regional expansion in Kadipiro Village was still not going well, where various problems were found in several phenomena. In the initial process of discussing the expansion policy proposal, there were a number of Kadipiro Village residents who rejected the proposal. Another problems that arisesoccurs in the technocratic process, as well as the dynamics of discussion among stakeholders where policy actors are aware that there is one of requirements that cannot be fulfilled for Kadipiro Village to continue regional expansion but the use of population indicators and PP Number 78/2007 as an additional assessmet measure which is then uses as a rationalization for the consideration to continue the policy. Besed on the discussion process, the agenda for setting up the expansion of Kadipiro Village is included in the persuasive model. As for the initiative and expansion of the issue, the agenda setting of Kadipiro Village included in a model of outside initiative model.